The pre-pandemic role of customer online satisfaction in price determination: Eevidence from hotel industry - Irena Palić; Petra Palić; Frane Banić (Croatian Review of Economic, Business and Social Statistics (CREBSS), 2021)
This study examines the importance of online reviews for price determination in the hotel industry in the pre-pandemic period. The research is conducted for Croatian small open economy with a developed tourism sector. The paper fills the gap in existing literature by using multivariate principal component analysis to group various customer satisfaction categories in the hotel industry and assessing the relationship between customer satisfaction and hotel price. The conducted empirical analysis points to a positive statistically significant relationship of guest satisfaction and hotel prices. Moreover, linear regression modelling is conducted separately for four-star and five-star hotels. The estimated impacts are statistically significant and positive, but the effects are twice as strong in five-star hotels then in four-star hotels. The obtained results indicate that hotel star rating impacts the strength of the relationship between hotel prices and guest satisfaction. Recognizing the link between hotel ratings, online reviews and pricing is essential both for hotel managers and customers. Hence, the paper provides valuable conclusions from the aspect of supply and demand side in the hotel industry.
Keywords: C38; L83; Z3; Z32; 330; customer satisfaction; hotel pricing; hotel star rating; multivariate analysis; principal component analysis; regression analysis